WEB-BASED HONEY HARVEST SCHEDULING IN THE MUARO BOTUAK JAYA (MBJ) GROUP - muhammad hafiz; Nuraeni Dahri; Harry Setya Hadi (Jurnal Manajemen Teknologi Informatika, 2023)
This research is motivated by the mechanism of the conventional honey harvesting system. The harvest schedule is carried out irregularly, resulting in honey that is less than the quality and quantity. Usually this problem can be resolved with an integrated information system that is effective and efficient in managing harvest scheduling. Systems Development Life Cycle (SDLC) SDLC method with a waterfall model approach. The design tools used in this information system are UML, which consists of usecase diagrams, class diagrams, sequence diagrams, activities, collaboration diagrams, implementation. The application used is My SQL database and the PHP programming language. The design of this system produces an information system in the form of a honey scheduling website for the Muaro Botuak Jaya group which was previously written manually to carry out scheduling and with this website the MBJ group can carry out scheduling more effectively and efficiently. Web-Based Honey Harvesting Scheduling System in the Muaro Botuak Jaya (MBJ) Group was built to overcome scheduling problems in the Muaro Botuak Jaya (MBJ) Group, Design of a Web-Based Honey Harvesting Scheduling System in the Muaro Botuak Jaya (MBJ).